2016
DOI: 10.1155/2016/2036234
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Challenges in Tuberculosis Control in West Gojjam Zone, Northwest Ethiopia: Health Workers’ and Tuberculosis Control Program Coordinators’ Perspectives

Abstract: Background. Weak health systems pose many barriers to effective tuberculosis (TB) control. This study aimed at exploring health worker's and TB control program coordinator's perspectives on health systems challenges facing TB control in West Gojjam Zone, Amhara Region, Ethiopia. Methods. This was a qualitative descriptive study. Eight in-depth interviews with TB control program coordinators and two focus group discussions among 16 health workers were conducted. Purposive sampling was used to recruit study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 23 publications
(22 reference statements)
14
32
1
Order By: Relevance
“…Our findings suggest that there were inadequate resources which were necessary for TB case finding. The findings are consistent with previous studies in Ethiopia which reported that there were inadequate resources, such as trained health-care providers and laboratory reagents for the TB control programs [12,39,40]. Inadequate or the absence of necessary resources might significantly hinder the provision of TB diagnostic services as expected, and cause TB case notification to become low in the study area.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings suggest that there were inadequate resources which were necessary for TB case finding. The findings are consistent with previous studies in Ethiopia which reported that there were inadequate resources, such as trained health-care providers and laboratory reagents for the TB control programs [12,39,40]. Inadequate or the absence of necessary resources might significantly hinder the provision of TB diagnostic services as expected, and cause TB case notification to become low in the study area.…”
Section: Discussionsupporting
confidence: 90%
“…Other qualitative studies also revealed similar barriers to TB control programs, such as a shortage of human resources, inadequate access to TB services, and transportation problems, were reported along the Thai-Myanmar border [58]; a shortage of resources, poor accessibility and a capacity for TB diagnosis, as well as a weak community involvement, were reported in Northern Malawi [59]. Moreover, a shortage of resources, and a lack of access to TB diagnostic services at peripheral health facilities, were reported in Northwest Ethiopia [40].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the integration of TB screening activities in the general health care and increased access in TB diagnostic and treatment services however, it is surprising that the median health system’s delay observed in the current study is still similar with findings of former studies conducted in Amhara Region of Ethiopia [6, 12]. In a recent qualitative study [22], a number of challenges that may have implications for increased health system’s delay were reported from the study area. Among others, frequent interruptions of laboratory reagents and anti-TB drugs supplies, lack of diagnostic tools for smear-negative TB and lack of laboratory personnel in some health centers were identified as challenges of the TB control program [22].…”
Section: Discussionsupporting
confidence: 84%
“…In a recent qualitative study [22], a number of challenges that may have implications for increased health system’s delay were reported from the study area. Among others, frequent interruptions of laboratory reagents and anti-TB drugs supplies, lack of diagnostic tools for smear-negative TB and lack of laboratory personnel in some health centers were identified as challenges of the TB control program [22]. Interventions directed at solving these challenges are essential to reduce the long health system’s delay observed in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation